GAMBARAN JENIS RISIKO PENGELOLAAN BANTUAN SOSIAL SELAMA PANDEMI COVID-19 DI INDONESIA - Wahyuari; Indra, I Made; Septivani, C. Nike; Kusdani, Dedi (Premium Insurance Business Journal, 2021)
Risk management is very important for the continuity of a business or activity. If a disaster occurs, such as fire or damage, the company will suffer huge losses, which can hinder, disrupt or even destroy business continuity or operations. Risk management is a tool to protect the company from any possible harm. So that in the management of logistical assistance, especially when a disaster occurs, both natural and non-natural, a risk management effort is needed in order to reduce the impact of losses in operations. This research uses explanatory type. The samples in this study were derived from elements of government, academia and society with qualitatively managed data. The results of the study found 8 risk categories that occurred in the logistical assistance process during the Covid-19 pandemic in Indonesia, namely: policy risk, compliance risk, legal risk, fraud risk, reputation risk, reputation risk and operational risk.